ANALISIS USAHA BUBUK KOPI MAK AMBIK DI KECAMATAN GUNUANG OMEH KABUPATEN LIMA PULUH KOTA SUMATERA BARAT (Analysis Of Mak Ambik Coffee Powder Business In Gunuang Omeh District Lima Puluh Kota West Sumatera) - FAUZI, WAHYUNI AHDA; HAFIZAH, DIAN; ANALIA, DEVI (Universitas Mulawarman (University of Mulawarman), 2023)
This study aims to describe the profile of the Mak Ambik coffee powder business in Gunuang Omeh District and to analyze the business conditions from the operational, marketing and financial aspects as well as knowing the business profits. This research uses a descriptive method with the type of case study research and financial calculations using the variable costing method. The data used are primary data and secondary data. Data collection was carried out by means of direct interviews with the head of the Mak Ambik coffee powder processing business, as well as literature related to research. This research was conducted on August 1, 2022 to August 31, 2022. The results showed that Mak Ambik's coffee powder business, seen from the human resource aspect, Mak Ambik's coffee powder business has 5 workers, seen from the marketing aspect of the Mak Ambik coffee powder business, price by calculating the capital that has been issued, promotion is done by way of personal selling and sales promotion. On the financial aspect, the initial capital of this business is Rp. 15,000,000 taken from personal funds, this business still keeps financial records manually and simply. During the study period, the business earned a profit of Rp. 9,466,410 with a percentage of 14.8%. This shows that this business has achieved profits from its business.